Bellmer's Argentine Doll: Alejandra Pizarnik and the Dis¬articulation of the Self - Melanie Nicholson (Studies in 20th & 21st Century Literature, 2008)
This essay argues that Alejandra Pizarnik (Buenos Aires, 1936-72), widely recognized as one of the most important figures of twentieth-century Spanish-American poetry, constructs a poetic self that bears a remarkable resemblance to the dolls of German surrealist sculptor and photographer Hans Bellmer. Both poet and artist portray the doll as a passive and melancholy figure, an object that is often dismembered and otherwise stripped of agency. I examine the distinct implications of such a figure for a male surrealist photographer and a female post-surrealist writer. By means of this comparison—admittedly complicated by vast differences in artistic medium and historical context—I hope to elucidate Pizarnik's construction of the poetic self, in particular her allusions to loss of selfhood through the tropes of doubling, deformation, and fragmentation. The essay concludes that while the doll/mannequin—or more broadly the representation of the immobilized, sometimes disarticulated female body—served for male surrealists like Bellmer as a site for the projection of desire, for Pizarnik it served as a site for the obsessive representation of damaged selfhood.
Keywords: Argentine; Alejandra Pizarnik; self; Spanish-American poetry; Hans Bellmer; agency; post-surrealism; poetic self; male surrealists